2011
DOI: 10.4049/jimmunol.1100500
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A Activates the NLRP3 Inflammasome and Promotes Th17 Allergic Asthma in Mice

Abstract: Interleukin (IL)-1β is a cytokine critical to several inflammatory diseases in which pathogenic TH17 responses are implicated. Activation of the NLRP3 inflammasome by microbial and environmental stimuli can enable the caspase-1 dependent processing and secretion of IL-1β. The acute phase protein serum amyloid A (SAA) is highly induced during inflammatory responses, wherein it participates in systemic modulation of innate and adaptive immune responses. Elevated levels of IL-1β, SAA, and IL-17 are present in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
225
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(237 citation statements)
references
References 69 publications
12
225
0
Order By: Relevance
“…When not associated with HDL, SAA is a stimulus for the production of cytokines, reactive oxygen species and NO [13][14][15]31]. SAA is also able to activate the inflammasome pathway, considered a mediator of the innate and adaptive immune system [32,33]. Furthermore, SAA is induced by hypoxia [22], a common event in fat expansion.…”
Section: Discussionmentioning
confidence: 99%
“…When not associated with HDL, SAA is a stimulus for the production of cytokines, reactive oxygen species and NO [13][14][15]31]. SAA is also able to activate the inflammasome pathway, considered a mediator of the innate and adaptive immune system [32,33]. Furthermore, SAA is induced by hypoxia [22], a common event in fat expansion.…”
Section: Discussionmentioning
confidence: 99%
“…We used gene-deficient mice and evaluated the role of IL-17A in CCl 4 -induced acute and chronic injury and HSC activation. IL-17A/IL-17RA signaling plays a critical role in autoimmune diseases such as asthma, arthritis, ulcerative colitis, and Crohn's disease (30)(31)(32)(33). IL-17A is involved in neutrophil recruitment and angiogenesis (34), and IL-17A expression is partially dependent on IL-1 and IL-23 signaling (8,35).…”
Section: Discussionmentioning
confidence: 99%
“…Saa3, is a major acute-phase protein that can act as a chemoattractant for phagocytes (35) and recently was shown to promote Th17-mediated allergic asthma through the activation of the NLRP3 inflammasome complex (36). Our data showed that this gene was significantly upregulated following Flu infection, with an additional 2-fold increase following HDM exposure during the EP that was sustained through the LP, where we observed a 5-fold difference in expression level between Flu-and Flu+HDM-treated mice (Tables VI, VII).…”
Section: Discussionmentioning
confidence: 99%